The Relative Role of Semantic and Sublexical Processes in Reading, Writing and Repetition: Evidence from a Follow-Up Study - Flavia Mattioli (Behavioural Neurology)
The evolution in time of a number of language tasks in a longitudinal study of a 61-year-old aphasic patient is described. The patient, examined twice, in a 10 month follow-up, showed a dissociation between preserved reading with respect to impaired other modalities as well as a qualitative change in errors' type. A reduction of neologisms and phonologically based errors, with a concurrent increase of semantic paraphasias in naming and repetition, as well as an amelioration in reading, with a reduction of stress assignment errors was exhibited at the follow-up. The results are interpreted by postulating an improved performance of the phonological output processes, allowing non-phonologically based errors to emerge, thus revealing the underlying semantic damage. The Summation Hypothesis [14] seems a general framework better interpreting these findings, more than highly specialized production models, which could explain separately only different modalities’ impairments.